REKOMENDASI PEMILIHAN MINAT TESIS MAHASISWA MENGGUNAKAN METODE FUZZY MAMDANI - , ASTRIE KUSUMA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study duration of the master students is three to four semesters. But in fact the study period students take more than four semesters. One of the obstacles faced in the process is the research thesis. Knowing earlier thesis interest of students in the beginning of semester, can help their ability students. This can be done among others by selecting the elective courses and joined to research that have been followed by who have the same interests. JTETI department have already built three research groups. Those groups were built aim to help the students with common thesis interest. The purpose of this study to determine research interests are in accordance with the interest and motivation of students using Mamdani fuzzy systems Questionnaire were developed for data collection. There were two kinds of questionnaires distributed to the respondents. It consisted of interest questionnaires and motivation questionnaires. The result of questionnaires werre the input data. After the data were collected, validity and reliability test were done to determine the extent to which the feasibility of questions on the questionnaire used as the data. Furthermore, were processed using the Mamdani method. It is one method of Fuzzy Inference System that was used to determine student interest based on fuzzy rules. From the results of the evaluation was known that as many as 51.06% of the students have the same interests with the thesis proposal and approximately 48.94% of students have an interest that was not in accordance with the student's thesis proposal.